TRAINING COMPETITIVE SPECIALISTS OF TECHNICAL UNIVERSITIES IN THE ENVIRONMENT OF DUAL EDUCATION - Жарова, О. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2017)
The article deals with the problem of competitiveness of higher education graduates of modern higher technical institutions by introducing dual education. A dual mode of study includes a combination of the theory at the higher education institution and practice at the enterprise. One of the most important educational tasks is to provide the future specialist with a workplace with the balancing of the demand and supply of specialists in the labor market. A combination of training and practice (work on a specialty) will facilitate the development of the necessary competences of a future specialist. The introduction of dual education involves a flexible organizational and managerial structure, innovative technologies and pedagogical approaches, as well as cooperation with leading enterprises and institutions